Aktivitas Antimikroba Dan Antioksidan Ekstrak Daun Hoya Lacunosa Blume Dan Hoya Diversifolia Blume - Mazia Natasya Aqilah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Plants from the Hoya genus are known to have potential as traditional medicinal plants to treat various health problems, including stomachaches, skin infections, and rheumatism. The content of secondary metabolites, such as phenolics, alkaloids, and terpenoids, in these plants is thought to play a role in their biological activities, particularly as antimicrobials and antioxidants. This study aimed to analyze the antimicrobial and antioxidant activities of Hoya lacunosa and Hoya diversifolia leaf extracts. Antibacterial activity was tested against Staphylococcus aureus using the agar well diffusion method at concentrations of 10-50%, followed by determination of the Minimum Inhibitory Concentration (MIC) using the liquid dilution method. Spectrum activity tests were conducted against Gram-negative bacteria (Salmonella typhimurium and Escherichia coli) and Candida albicans. Antioxidant activity was analyzed using the DPPH method, and IC₅₀ values were determined through a linear regression equation. The results showed that H. lacunosa extract at a concentration of 10-50% was able to inhibit the growth of S. aureus with a moderate to strong category (7.08-13.34 mm), while, H. diversifolia showed moderate to very strong category (10.48-23.13 mm). The MIC values for both extracts were obtained at a concentration of 12.5%. Spectrum testing showed that at 50% concentration, both extracts were classified as a broad spectrum inhibitor, capable of inhibiting Gram-positive bacteria (S. aureus) and Gram-negative bacteria (S. typhimurium and E. coli), also C. albicans. In the antioxidant test, H. lacunosa and H. diversifolia extracts had IC₅₀ values of 36.18 ppm and 43.73 ppm, respectively, which are considered very strong, although still lower than vitamin C (7.74 ppm). Both extracts showed potential as natural antimicrobial and antioxidant agents, although not as effective as the antibiotic chloramphenicol 1% and vitamin C
Validasi dan Finalisasi Ratna 1 Juli 2026
Keywords: Antimikroba; Antioksidan